Geometric Morphometric Analysis in Human Craniofacial Research: Diagnostic Value and Clinical Implications – A Systematic Review - Gita Dwi Jiwanda Sovira; Erli Sarilita (Jurnal EduHealth, 2025)
Background: Geometric morphometric analysis has become an essential quantitative approach for evaluating complex craniofacial morphology beyond traditional linear measurements. Advances in three-dimensional imaging have expanded its application in diagnosis, treatment planning, and outcome assessment in craniofacial and dental practice. However, a comprehensive synthesis of its clinical relevance remains limited. Method: This systematic review was conducted in accordance with PRISMA 2020 guidelines. Literature searches were performed in PubMed, Scopus, and Google Scholar for articles published between 2019 and 2024. Eligible studies included original research involving human subjects that applied geometric morphometric analysis to craniofacial structures with reported diagnostic or therapeutic relevance. Study selection, data extraction, and qualitative synthesis were performed independently. Results: Eight studies met the inclusion criteria. The findings demonstrated that geometric morphometrics is widely applied in odontological analysis and orthognathic surgery. Applications in forensic and anthropological research further highlighted its utility in population and individual identification. Conclusion: Geometric morphometric analysis provides a objective framework for craniofacial diagnosis and treatment planning. Its integration with three-dimensional imaging technologies enhances diagnostic accuracy and supports data-driven clinical decision-making. Future studies should focus on protocol standardization and large-scale clinical validation to facilitate broader implementation in routine practice.